In the shadows of Paris the Nazi concentration camp that dimmed the city of light - Sinclair, Anne 1948- (Norton, 2021)
"'This story has haunted me since I was a child,' begins Anne Sinclair in a personal journey to find answers about her own life and about her grandfather's, Léonce Schwartz. What her tribute reveals is part memoir, part historical documentation of a lesser known chapter of the Holocaust: the Nazi's mass arrest, in French the word for this is rafle and there is no equivalent in English that captures the horror, on Dec. 12, 1941 of influential Jews--the doctors, professors, artists and others at the upper levels of French society--who were then imprisoned just fifty miles from Paris in the Compiègne-Royallieu concentration camp. Those who did not perish there, were taken by the infamous one-way trains to Auschwitz; except for the few to escape that fate. Léonce Schwartz was among them"--
Originally published as "La rafle des notables" by Éditions Grasset & Fasquelle, 2020
Keywords: Schwartz, Léonce -- 1878-1945; Internierungslager Compiègne; Geschichte 1939-1945; Zweiter Weltkrieg; Judenverfolgung; Paris; Schwartz, Léonce; Royallieu (Transit camp) / Biography; Nazi concentration camp inmates / France / Compiègne / Biography; World War, 1939-1945 / Prisoners and prisons, French; Jews / France / Paris / Biography; Holocaust, Jewish (1939-1945) / France; Nazi concentration camps / France / History; Paris (France) / Biography; Royallieu (Transit camp); Nazi concentration camp inmates; Jews; Nazi concentration camps; France; France / Compiègne; France / Paris; 1939-1945; Biographies; History